Malaria Policy - Malawi Government: Ministry of Health (Malawi Government, 2021)
Maiaria is the leading cause of morbidity and mortality, particularly in children under five years of age and pregnant women. It is the commonest cause of outpatient visits, hospitalisation and death. Malaria is also a development problem as it has a serious socio economic impact on families and the nation,, through loss of work, school absenteeism and high levels of expenditure on malaria treatment, especially by poor households, This policy marks an important milestone in malaria control and prevention in Malawi. Organised malaria control efforts started in 1984 with the establishment of the National Malaria Control Programme (NMCP) to spearhead the struggle against malaria as part of the response to the emergence of chloroquine-resistant Plasmodium falciparum. The NMCP led a systematic study of the efficacy of chloroquine and other antimalarial drugs. This resulted in the development of editions of guidelines for the management of malaria in ; vS5, 1936, 1994 and 1997. In the absence of a policy to guide activities, efforts and resources by the Ministry of Health and Population (MOHP) and partners nationwide, malaria control and prevention strategies and activities have been uncoordinated and incomplete. The launching of the Roll Back Malaria (RBM) movement through the Abuja Declaration, which was signed bv Alncan Heads of State and Government ;n April 2000, gave malaria a high profile globally, regionally and nationally. To achieve the Abuj a targets, RBM calls for concerted efforts through the development of partnerships. The expected increased number of stake holders in malaria makes a policy essential. The policy covers the main areas of malaria control and prevention, namely effective case management, especially in children under five years of age, use of insecticide-treated nets and other vector control measures as well as operational research and information, educa tion and communication. The policy also addresses crosscutting issues such as manage ment, financing and human resources; without improvement in these areas, enhanced nitiana control and prevention efforts will not succeed. The fourth National Health Plan emphasises the need to improve the health status of all people in Malawi by "strengthening coordination and collaboration between all health partners in supporting the district health care delivery structure as the main health care delivery system". The policy has been developed within the context of essential health care peekage and sector-wide approaches.